(3GddeYs - (3EHQGgje Hf Ydj Hf jhSa GdTjQGRj GdajQhRGHGOj , CHh ESMGb , LeGd GdOjf,J (B476 (3g` s
(3ChdgG (B:s
(3GdMeO ddg ceG gh Cgdg SCdfi HYV ENhGfi Cf CfUa dg eNJUQkG ai GdePgH ai CUhd Gdabg djchf Pdc eVGakG Edi eG Yedg ef GdJHUQI ai GdNdGa HGH HjGf GdYde s
(3BNQgG (B:s
(3hbGd CcKQ GdbOQjI dGjLhR hgPG NWC dCfg djS ai JLhR Pdc EMGdg ced cJGH GddeY ddTjQGRi HMeO Gddg hMSf Yhfg hUdi Gddg Ydi eMeO hYdi Bdg hSde JSdjekG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B51 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B68s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B410s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs